2021
DOI: 10.1136/bmjno-2021-000199
|View full text |Cite
|
Sign up to set email alerts
|

DelIrium VULnerability in GEriatrics (DIVULGE) study: a protocol for a prospective observational study of electroencephalogram associations with incident postoperative delirium

Abstract: IntroductionDelirium is a neurocognitive disorder common in older adults in acute care settings. Those who develop delirium are at an increased risk of dementia, cognitive decline and death. Electroencephalography (EEG) during delirium in older adults is characterised by slowing and reduced functional connectivity, but markers of vulnerability are poorly described. We aim to identify EEG spectral power and event-related potential (ERP) markers of incident delirium in older adults to understand neural mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…Persistent resting-state EEG slowing in frequency was seen at four months [ 151 ] and one year [ 152 ] following hospital discharge among older adults in two studies, while one study found an overall normalization of quantitative resting-state EEG patterns at one month after discharge in a majority of people who had delirium [ 60 ] (Table 6 ). Further longitudinal studies are required to determine if delirium is associated with long-term EEG changes, and additional studies of this type are currently underway [ 153 ].…”
Section: Eeg Recorded Following Delirium Resolutionmentioning
confidence: 99%
“…Persistent resting-state EEG slowing in frequency was seen at four months [ 151 ] and one year [ 152 ] following hospital discharge among older adults in two studies, while one study found an overall normalization of quantitative resting-state EEG patterns at one month after discharge in a majority of people who had delirium [ 60 ] (Table 6 ). Further longitudinal studies are required to determine if delirium is associated with long-term EEG changes, and additional studies of this type are currently underway [ 153 ].…”
Section: Eeg Recorded Following Delirium Resolutionmentioning
confidence: 99%
“…A limitation of this review is the exclusion of non-functional connectivity EEG measures, including EEG power. We chose to exclude these studies as the paper by Boord et al (2021a , b) had already covered this area in depth. Another potential limitation is the exclusion of studies that measured functional connectivity without using EEG, including studies of fMRI and magnetic electroencephalography (MEG).…”
Section: Discussionmentioning
confidence: 99%